1999
DOI: 10.1002/jor.1100170108
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy: Adenovirus‐mediated human bone morphogenetic protein‐2 gene transfer induces mesenchymal progenitor cell proliferation and differentiation in vitro and bone formation in vivo

Abstract: This study reports that recombinant adenovirus-mediated human bone morphogenetic protein-2 gene transfer can induce mesenchymal progenitor cell differentiation and bone formation. The recombinant adenovirus with the human bone morphogenetic protein-2 gene was constructed, and mature human bone morphogenetic protein-2 expression mediated by adenovirus gene transfer was detected by specific antibody. Under adenovirus-mediated bone morphogenetic-protein gene transfer, mesenchymal progenitor cell line C3H/10T 1/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
129
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(138 citation statements)
references
References 25 publications
9
129
0
Order By: Relevance
“…BMP-2, approved by Food and Drug Administration (FDA) for clinical practice, is the most potent member in promoting bone and cartilage development and therefore wins a popular choice for MSCs-based BTE (Lieberman et al, 1998;Lieberman et al, 1999;Lou et al, 1999;Turgeman et al, 2001;Olmsted-Davis et al, 2002;Blum et al, 2003;Gugala et al, 2003;Park et al, 2003;Riew et al, 2003;Tsuda et al, 2003;Kumar et al, 2004;Hasharoni et al, 2005;Egermann et al, 2006;Feeley et al, 2006). The BMP-2-modified MSCs are proven to increase the alkaline phosphatase (ALP) activity, mineralization, and cell proliferation in vitro and induce ectopic bone formation, heal critical size bone defect, repair fracture, and trigger spinal fusion in vivo (Lou et al, 1999;Moutsatsos et al, 2001;Turgeman et al, 2001;Blum et al, 2003;Park et al, 2003;Riew et al, 2003;Tsuda et al, 2003;Hasharoni et al, 2005;Egermann et al, 2006;Feeley et al, 2006). BMP-7 plays a key role in osteoblast differentiation, and there is only one study in which MSCs are engineered with BMP-7.…”
Section: Applicable Genes For Mscs Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP-2, approved by Food and Drug Administration (FDA) for clinical practice, is the most potent member in promoting bone and cartilage development and therefore wins a popular choice for MSCs-based BTE (Lieberman et al, 1998;Lieberman et al, 1999;Lou et al, 1999;Turgeman et al, 2001;Olmsted-Davis et al, 2002;Blum et al, 2003;Gugala et al, 2003;Park et al, 2003;Riew et al, 2003;Tsuda et al, 2003;Kumar et al, 2004;Hasharoni et al, 2005;Egermann et al, 2006;Feeley et al, 2006). The BMP-2-modified MSCs are proven to increase the alkaline phosphatase (ALP) activity, mineralization, and cell proliferation in vitro and induce ectopic bone formation, heal critical size bone defect, repair fracture, and trigger spinal fusion in vivo (Lou et al, 1999;Moutsatsos et al, 2001;Turgeman et al, 2001;Blum et al, 2003;Park et al, 2003;Riew et al, 2003;Tsuda et al, 2003;Hasharoni et al, 2005;Egermann et al, 2006;Feeley et al, 2006). BMP-7 plays a key role in osteoblast differentiation, and there is only one study in which MSCs are engineered with BMP-7.…”
Section: Applicable Genes For Mscs Modificationmentioning
confidence: 99%
“…When engineered MSCs are implanted to thigh muscles (Lou et al, 1999;Dayoub et al, 2003;Li et al, 2003) or paraspinal muscles (Dumont et al, 2002;Hasharoni et al, 2005), ectopic bone formation is observed. Indeed, skeletal muscle injection is an optimal method in testing the viability and function of genetically engineered MSCs in vivo.…”
Section: Skeletal Muscle Injectionmentioning
confidence: 99%
“…[14][15][16] This approach would obviate the need for long-term selection of stable clones that may potentially lead to senescence, lost of multilineage differentiation capacity and lost of migratory potential of BM-hMSCs. The development of an efficient gene delivery vector to achieve high expression of therapeutic genes in BM-hMSCs is needed.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The multipotential of MSCs, their relatively easy isolation, culture and ex vivo expansive potential have attracted considerable attention in efforts to develop cell and gene therapies and have made these cells an attractive therapeutic tool in a wide range of clinical applications. 6 During the past decade many different viral vectors including retrovirus, 7 adenovirus, [8][9][10][11][12][13] lentivirus [13][14][15][16] and adeno-associated virus 13,[17][18][19][20] have been utilized to deliver genes to or modify genes in MSCs. Although the viral gene delivery to MSCs has made an impressive advancement toward clinical applications, 21 several drawbacks exist.…”
Section: Introductionmentioning
confidence: 99%